Современные направления научных исследований в женском спорте - Калытка, С.; Kalytka, S. (Східноєвропейський національний університет ім. Лесі Українки, 2010)
В статье представлены современные направления научных исследований в женском спорте, которые раскрывают особенности адаптационных реакций организма спортсменок к специфическим нагрузкам. The article deals with the current trends of women sports scientific investigation which reveal the peculiarities of adaptive reactions of sportswomen’s organism to specific loadings.
Current Trends of Women Sports Scientific Investigation
Keywords: женский спорт; менструальный цикл; фазы менструального цикла; научные исследования; women’s sports; menstrual cycle; menstrual cycle phases; scientific investigation